1998
DOI: 10.1002/ana.410430610
|View full text |Cite
|
Sign up to set email alerts
|

Temporal ictal electroencephalographic frequency correlates with hippocampal atrophy and sclerosis

Abstract: We studied 328 complex partial seizures (CPS) in 63 consecutive patients with temporal lobe epilepsy who underwent scalp electroencephalography/video monitoring, magnetic resonance imaging (MRI), and surgery. The initial ictal discharge (IID), defined as the first sustained electrical seizure pattern localized to the surgical site, was determined. If the IID was rhythmic waves, the median frequency was measured. To determine if IID frequency correlates with hippocampal atrophy (HA) or sclerosis (HS), hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 51 publications
4
34
0
Order By: Relevance
“…[22][23][24][25][26][27][28][29][30][31] These methods are superior to visual inspection of MR images. 32 Hippocampal volumetric analysis with MRI is not always able to detect hippocampal sclerosis accurately, 33 however, in those cases the additional analysis of entorhinal cortex volume or volume ratio analysis may be able to provide accurate lateralization of seizure focus (see Bernasconi et al 34 and Vossler et al, 35 respectively). These methods have demonstrated considerable efficacy, especially with the addition of T2 relaxation time data.…”
Section: Temporal Lobe Epilepsymentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31] These methods are superior to visual inspection of MR images. 32 Hippocampal volumetric analysis with MRI is not always able to detect hippocampal sclerosis accurately, 33 however, in those cases the additional analysis of entorhinal cortex volume or volume ratio analysis may be able to provide accurate lateralization of seizure focus (see Bernasconi et al 34 and Vossler et al, 35 respectively). These methods have demonstrated considerable efficacy, especially with the addition of T2 relaxation time data.…”
Section: Temporal Lobe Epilepsymentioning
confidence: 99%
“…1,4 Hippocampal sclerosis is implicated as the cause of seizures and also associated cognitive deficits and seizure intractability, in patients with TLE. 3,[5][6][7][8] Hippocampal sclerosis is less common in children than adults with TLE, but may nevertheless be present in up to half or more patients. 9 -11 Pathology and neuroimaging studies have suggested seizures in children are the precipitant of hippocampal sclerosis, and hippocampal sclerosis the cause of TLE.…”
mentioning
confidence: 99%
“…22 Consequently, doserelated reduction of h-activity in the left temporal region could be explained as cortical and limbic, particularly, hippocampal damage. [23][24][25][26][27] Dose-related diffusive depression of ␣-power in the EEG PATTERNS AND IONIZING RADIATION frame of current neurophysiological theories could be outlined as 1) thalamic, 2) thalamocortical, 3) cortical, 4) hippocampal and/or 5) diffusive brain damage. 28 Diffusive reduction of b-power in confirmed ARS patients could be explained as dysfunction (inhibition) of corticocortical and thalamocortical transactions 19 and decreased thalamic and nucleus caudate input on cortex.…”
Section: Discussionmentioning
confidence: 99%